Teachers’ Attributes and Capabilities in the Delivery of the New K-10 Curriculum in Selected Junior High Schools in the Division of Manila - Salazar, Nilo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the attributes and capabilities of Grade 7 and 8 teachers in delivering the MATATAG K–10 curriculum in selected public secondary schools in the Schools Division Office of Manila. Anchored on Keane’s Theory of Action and supported by pedagogical content knowledge frameworks, the study utilized a descriptive-correlational research design to analyze the relationships between teachers’ profile variables, professional attributes, and instructional capabilities. A total of 156 teachers were selected through purposive and multistage proportionate sampling. Data were collected using a validated researcher-developed questionnaire with a reliability coefficient of 0.86 and were analyzed using descriptive statistics and Pearson Product–Moment Correlation. Findings revealed that teachers demonstrated high to very high levels across all attributes, particularly in passion for teaching, emotional intelligence, and creative problem-solving, and were highly capable in content knowledge and pedagogy, diversity of learners and assessment, curriculum and planning, and community engagement. Most profile variables were not significantly related to teacher capabilities, except for highest educational attainment and present position in selected domains. In contrast, all teacher attributes showed strong and significant relationships with all capability areas, indicating that professional attributes are key determinants of instructional effectiveness. The study concludes that strengthening teacher attributes is essential for effective curriculum implementation and recommends sustained professional development, advanced academic pursuit, and structured support systems for teachers. This study aligns with SDG 4 (Quality Education) by promoting teacher quality and effective instruction, and supports SDG 8 (Decent Work and Economic Growth) through the development of competent educators. The findings contribute to educational and institutional sustainability by informing policy, enhancing teacher development, and improving instructional practices that support long-term learning outcomes.